2023
DOI: 10.31234/osf.io/jxznd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social dynamics and affect: Investigating within-person associations in daily life using experience sampling and mobile sensing

Abstract: Social interactions are crucial to affective well-being. Still, people vary interindividually and intraindividually in their social needs. Social need regulation theories state that mismatches between momentary social desire and actual social contact result in lowered affect, yet empirical knowledge about this dynamic regulation is limited. 306 participants in a sample stratified by age and gender (51% women, M_age = 39.41, range 18-80 years) answered up to 20 questionnaires about social interactions and affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…For example, daSilva et al ( 2021) used microphone logs to estimate conversation times and found that selfreported stress was associated with reduced social interaction the next day; however, conversation times on a given day did not predict stress levels on the following day. Krämer et al, (2023) provided another example for how this powerful combination of methods can be used.…”
Section: Social Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, daSilva et al ( 2021) used microphone logs to estimate conversation times and found that selfreported stress was associated with reduced social interaction the next day; however, conversation times on a given day did not predict stress levels on the following day. Krämer et al, (2023) provided another example for how this powerful combination of methods can be used.…”
Section: Social Behaviorsmentioning
confidence: 99%
“…They investigated social dynamics in relation to momentary affect. Their mobile sensing results pointed to the importance of face-to-face conversations in daily life: While a higher frequency in communication app use was associated with higher negative affect when alone, self-reported levels of positive affect at a moment when individuals were in social contact or alone were higher when they had more in-person conversations (detected via microphone logs) in the preceding situations (Krämer et al, 2023).…”
Section: Social Behaviorsmentioning
confidence: 99%
“…In the context of this study, within-person effects would reflect how an individual's smartphone usage and momentary well-being fluctuate within the same person, while between-person effects would reflect how individuals differ in their average smartphone usage and momentary well-being across the whole study period (Bolger & Laurenceau, 2013). Examining within-person effects, in which we compare measures to how the same participant usually behaves, can help us to better understand the underlying micro-level processes of the relationship between smartphone usage and momentary well-being (Krämer et al, 2023;Lin & Lachman, 2021). The few studies that investigate the association between smartphone usage and momentary well-being on a within-person level show mixed evidence for the presence of such effects ( Große Deters & Schoedel, 2023;Krämer et al, 2023;Lin & Lachman, 2021;Marciano et al, 2022).…”
Section: How To Measure Immediate Changes In Well-beingmentioning
confidence: 99%
“…Examining within-person effects, in which we compare measures to how the same participant usually behaves, can help us to better understand the underlying micro-level processes of the relationship between smartphone usage and momentary well-being (Krämer et al, 2023;Lin & Lachman, 2021). The few studies that investigate the association between smartphone usage and momentary well-being on a within-person level show mixed evidence for the presence of such effects ( Große Deters & Schoedel, 2023;Krämer et al, 2023;Lin & Lachman, 2021;Marciano et al, 2022).…”
Section: How To Measure Immediate Changes In Well-beingmentioning
confidence: 99%
See 1 more Smart Citation